Can paraoxonase activity serve as a comparable marker than high density lipoprotein in the follow-up of patients of coronary artery disease?. (4th February 2022) - Chatterjee, S; Majumder, B; Biswas, P; Sarkar, S; Sinha, P K; Mukhopadhyay, L; Chakraborty, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Human serum paraoxonase (PON1) produced by the liver and residing almost exclusively on high density lipoproteins (HDL), has been demonstrated to prevent the oxidation of low density lipoprotein (LDL), which is  the central initiating factor in the causation of atherosclerosis. (1, 2) Thus, PON1 along with HDL, plays an important role in the pathophysiology of atherosclerosis and consequently coronary artery disease. Statins are commonly used in clinical practice for the management of dyslipidemia, a known risk factor for coronary artery disease (CAD).Keeping this in mind,   it was deemed necessary to set up an observational study to explore whether the changes in PON1 activity after 3 months of statin therapy could help in the follow up of CAD patients. Purpose: The purpose of the study was to evaluate the alterations in the PON1 activity along with the concentrations of HDL and LDL in patients of CAD before and after 3 months of statin therapy and to explore whether PON1 can be used as a comparable marker for assessment of the atherosclerotic risk in the follow up of these patients. Materials and Methods: The study included 30 new patients who were put on statin therapy following the diagnosis of acute coronary syndrome in the Cardiology outpatients department. The activity of PON1 and the lipid profile parameters were estimated before starting statin therapy and again three months later. Patients with co-morbidities like diabetes, chronic kidney disease, chronic liver disease and other cardiac diseases of infectious etiology were excluded from the study. The data thus obtained was compiled and tabulated in Excel and statistically analyzed. Results: The mean, median and standard deviation of the PON1, LDL and HDL, both before and after starting statin therapy, were calculated and the distribution of the individual parameters were determined. Analysis of the compiled data revealed that there was a statistically significant increase in both PON1 (p < 0.05) and HDL (p < 0.001) and a decrease (p <0.05, also statistically significant) in LDL after 3 months of statin therapy. The results both before and after 3 months of statin therapy are summarised in the table attached.(Table 1) Conclusion: It may be concluded from the above study that the activity of PON1 may be used to indicate the changes in the lipid profile in the follow up of patients of CAD being treated with statins. It is however necessary to conduct larger, well designed studies in future to explore whether it may be used as a comparable marker better than HDL in the follow up of these patients.